Prevalence of dental fluorosis and dental caries in fluoride endemic areas of Rohtak district, Haryana - Reena Rani; Ruchi Singhal; Parul Singhal; Ritu Namdev; Neha Sikk; Shruti Jha; Nancy Goel (Wolters Kluwer Medknow Publications, 2022)
Objectives: This study investigates the estimation of the fluoride concentration in drinking water in Rohtak district, Haryana, and quantifies its effect on the prevalence of dental fluorosis and dental caries. Materials and Methods: A cross-sectional survey was conducted among 1262 school children in endemic fluoride areas of Haryana. Using simple random sampling, thirty villages from five blocks of Rohtak districts were selected, and children 6-12 years of age were examined. A questionnaire survey form was filled out to record the demographic details of the samples. Dental caries was recorded according to DMFT (D = Decayed, M = Missing due to caries only, F = Filled, T = Teeth)/deft index (d = decayed, e = extracted due to caries, f = filled, t = teeth). Assessment of Dental Fluorosis was done according to Dean's Fluorosis index, modified in 1942. The data were analyzed using SPSS version 19, and nonparametric tests were used to assess the significance. Results: The study participants included 615 males and 647 females among which Mean DMFT in the area of study ranged from 0.32 to 1.90. Mean deft in the area of study ranged from 0.34 to 1.91. The fluoride concentrations in groundwater are in the range of 0.532-8.802. Out of 1262 children examined, 655 (51.90%) children were having dental fluorosis. 607 (48.10%) of the subjects were free from fluorosis. 16.09%, 13.39%, 9.11%, and 8.16% and 5.15% were having questionable, very mild, mild, moderate, and severe form of fluorosis, respectively. Conclusion: It can be concluded that in Rohtak district, the fluoride levels in drinking water and the prevalence of dental fluorosis are high, so requiring an urgent need to improve the quality of water and institute de-fluoridation of drinking water in affected areas to lower the burden of dental fluorosis in the community.